(untitled) (Global Journal of Medical Research, 2020)
World-wide poultry production is increasing day by day. One of the problems encountered in poultry production is disinfection. There are many microorganisms such as bacteria, viruses, fungi and parasites in the incubators. These microorganisms have negative effects such as the incubation of eggs incubated in the embryonic period, low chick weight, and poor chick quality. These effects lead to significant economic losses in commercial production. There are many disinfection applications to prevent these economic losses. In this study, the effects of antimicrobials on Japanese quail eggs in the embryonic period were investigated. The study control group consists of the 4th group as Greencop-Pro1, Greencop-Pro2 and Nano-Aq. There are 100 eggs for each group and 400 eggs for recurrence.In the study, a total of 1200 Japanese quails were used for 3 recurrences. For each antimicrobial 1 liter, 25 mg / kg x 5 was diluted to 25 mg / kg.